Hues of Protest: Graffiti and Street Art in Beirut (KULT_online, 2024)
Nadine Sinno’s A War of Colors, a study of street art and graffiti in postwar Beirut, is the first of its kind. Drawing on Bakhtinian concepts and theories of embodiment to complement her field work in Beirut, Sinno situates her work within the existing scholarship on visual culture in the Arab world. The book focuses on how the streets of Beirut are a space for protest, the reclaming of space, and a dialogical conversation with the city and its components. The book succeeds in many of its endeavors, but falls short in its simplistic representation of the complex socio-political landscape of post-war Beirut.